Effect of Tetracycline Antibiotics on Performance and Microbial Community of Algal Photo-Bioreactor - Taskan, Ergin (Humana Press Inc, 2016)
Tetracycline antibiotics have been increasingly used in medical applications and have been found in wastewater treatment plants as a result of human and industrial activities. This study investigates the combined effects of tetracycline antibiotics on the performance of an algal photo-bioreactor operated under different antibiotic concentrations in the ranges of 0.25 to 30 mg/L and considers the inhibition of algal growth, carbon and nutrient removal rates, and eukaryotic and cyanobacterial algal community changes. The results indicated that increases in the concentration of tetracycline mixtures have adverse effects on the algal community and the performance of a photo-bioreactor, and the eukaryotic algae species were more sensitive to tetracycline antibiotics than were the cyanobacterial species. Cultivation tests showed that approximately 94 % growth inhibition of mixed algae occurred at 30 mg/L.
Keywords: Mixed algae culture; Photo-bioreactor; Tetracycline antibiotics; Cyanobacteria; Eukaryotic algae; PCR-DGGE